Integrative and Complementary Practices: access bars to consciousness as a health care strategy (Research, Society and Development, 2020)
Objective: to present the benefits of Integrative and Complementary Practice - Access Bars for Consciousness. Methodology: this is an analytical bibliographic review study. Electronic searches were performed on the Access Consciousness website, based on studies developed by researchers and creators of this care practice. Results: the main results showed that the practice of Access Bars to Consciousness releases conditions and schedules that cause beliefs, limitations and discomfort. Promotes a feeling of lightness, peace and inner harmony; deep relaxation and pain relief in the body; slows down the mind; decreased anxiety, stress and compulsion; increase in mental clarity, self-confidence and self-esteem; improves the way of dealing with problems and everyday situations, bringing more awareness of the situation; helps to release memories of trauma and conditioning created since childhood; improves sleep pattern, fights anxiety, depression, stress, migraine, panic attacks, abuse and health problems. Conclusion: the practice brings several health benefits, however few studies have been published to demonstrate the effectiveness of the Access Bars to Consciousness. Thus, it is essential that professionals, especially health professionals, can use this care strategy, thus being able to publish their experiences and studies.